Activity Theory as a lens to understand how Facebook develops knowledge application skills - Bagarukayo, Emily; Ssentamu, Proscovia; Mayisela, Tabisa; Brown, Cheryl (International Journal of Education and Development using ICT, 2016)
Uganda’s higher education system has generally been criticized for concentrating on theory leading to a mismatch between training received and practical skills required by employers. Studies have documented the inability of graduates from some programmes at Makerere University in applying knowledge in the work environment. This could partly be attributed the use of traditional teaching methods, which do not adequately develop higher order cognitive skills and knowledge application in real life situations. Therefore, the study explored how technological approaches can be adopted to produce better graduates with ability to apply knowledge in real life situations. The study aimed to explore 1) how Facebook affords students to transfer knowledge acquired in the lecture room to the workroom and 2) the usefulness of Activity Theory (AT) as a lens to analyze how students interact with Facebook to develop knowledge application skills. Current methods of knowledge application were reviewed to identify gaps, strengths and effectiveness of Facebook learning activities guided by AT which is a useful social learning theory for studying transfer and knowledge application in new contexts among activity systems. Second year Bachelor of Information Technology students interacted with Facebook as a mediating tool to post videos installing an operating system on the page and interact with peers and their lecturer. Analysis of students’ interaction with Facebook activities, practices and implications, and the potential of AT for research, development and dissemination is presented. Findings show the usefulness of AT in clarifying how interactions in Facebook and contradictions occur. Finally, limitations of using AT in understanding how Facebook develops knowledge application skills and recommendations for future research are highlighted.
Keywords: Activity Theory; Facebook; knowledge